Determinan Kinerja Keuangan Perusahaan Batubara yang Terdaftar di BEI - Ade Andri Setyaningsih; Ismunawan Ismunawan (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The aim of this research is to determine the influence of HBA, DAR, DER, TATO and CR on the financial performance of coal companies. In this research, secondary data was used in the form of financial reports. There are 23 coal companies registered on the IDX as a population by taking samples using a purposive sampling method so that a sample of 4 companies is obtained. This research uses classical assumption testing methods, multiple linear regression analysis, and hypothesis testing. The results of the research conducted show that all independent variables simultaneously have an influence on stock prices. Partially, TATO influences financial performance. HBA, DAR, DER and CR have no effect on financial performance.